Online mathematics learning experiences of the colleges of education students in Ghana - Isaac Bengre Taley; Farouq Sessah Mensah; Philip Acheampong Adjei (Intelektual Pustaka Media Utama, 2021)
The dominant mode of instructional delivery in Ghanaian Colleges of Education has been the conventional face-to-face. However, the second semester of the 2019/2020 academic year teaching had to be done via an emergency remote online teaching mode due to the novel covid-19 pandemic. In a cross-sectional survey, the online mathematics learning experienced of 497 students sampled from three Colleges of education in Ghana were explored using the adapted community of inquiry survey instrument. It was observed from the study that students’ online mathematics learning experiences were low. Further observation showed that while class cohesion and resolution dimensions were absent, teaching presence, exploration, affective expression, and triggering event dimensions of students’ online mathematics learning experiences were present. Additionally, the results showed that the difference in the magnitude of means in gender was partly dependent on the category of internet use before the remote online mathematics teaching was observed in the dimension of lack of class cohesion. Besides, the students were generally indifferent in their learning experiences regarding genders but significantly in terms of their internet use before the remote online mathematics teaching. Based on the results, implications of the state of the college of education (CoE) students’ online mathematics learning experiences and suggestions for improvement have been proposed.